The Yoga Sutra of Patanjali: A Biography, by David G. White. (1st August 2018) - Powell, Seth
Abstract : The Yoga Sutra of Patanjali: A Biography, by David G. White. Princeton, NJ: Princeton University Press, 2014. xvii + 273 pp., $24.95. ISBN 978-0-691-14377-4 (hb).